Investigating the inner controls on explosive eruptions using textural analyses and petrology - Bernard, Olivier (Nanyang Technological University, 2022)
During an eruption, the level of threat a volcano poses to its surroundings is related to the style of activity. An effusive eruption generating slow-moving lava flows will be a lot less destructive than a violent explosive eruption producing large pyroclastic density currents (PDC). Recently, it has been shown that most volcanoes around the globe and particularly in a subduction-setting, are able to produce both effusive and violently explosive eruptions with sometimes rapid transitions between eruption styles in the span of a few hours to minutes. However, predicting how a volcano will erupt proves challenging.